2015
DOI: 10.1038/srep11579
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of Graphene/Carbon nanotube hybrid reinforced Al2O3 composites

Abstract: Tribological performance of the hot-pressed pure Al2O3 and its composites containing various hybrid contents of graphene nanoplatelets (GNPs) and carbon nanotubes (CNTs) were investigated under different loading conditions using the ball-on-disc method. Benchmarked against the pure Al2O3, the composite reinforced with a 0.5 wt% GNP exhibited a 23% reduction in the friction coefficient along with a promising 70% wear rate reduction, and a hybrid reinforcement consisting of 0.3 wt.% GNPs + 1 wt.% CNTs resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 22 publications
(35 reference statements)
3
42
0
Order By: Relevance
“…It can be found that at a relatively low content of 25 wt% WF, the performance of composites outperformed that of pristine PP, while deteriorated at high WF fraction. These outcomes are much consistent with the previous study that revealed a significant enhancement of wear resistance of resultant hybrid at an appropriate weight percentage of filler [45]. In fact, the unreinforced PP showed a degraded wear resistant property because of its poor mechanical properties that leads to intense grain pull-outs.…”
Section: Resultssupporting
confidence: 91%
“…It can be found that at a relatively low content of 25 wt% WF, the performance of composites outperformed that of pristine PP, while deteriorated at high WF fraction. These outcomes are much consistent with the previous study that revealed a significant enhancement of wear resistance of resultant hybrid at an appropriate weight percentage of filler [45]. In fact, the unreinforced PP showed a degraded wear resistant property because of its poor mechanical properties that leads to intense grain pull-outs.…”
Section: Resultssupporting
confidence: 91%
“…Generally, the wear of Si/Diamond pair is dominated by mechanical wear, which is governed by the processes of deformation and fracture. Therefore, such wear behavior is strongly associated with surface mechanical properties2930. Table 1 shows that the mechanical properties (hardness, elastic modulus) for the three crystal planes can be ranked by: Si(111) > Si(110) > Si(100)2429.…”
Section: Resultsmentioning
confidence: 99%
“…A load of 10 N, stroke length of 5 mm and sliding speed of 10 mm/s were used. In a previous publication, it was reported that the above loading conditions can produce suitable wear tracks in bulk alumina [17]. Wear tracks were measured using a Talysurf Form 50 contact profilometer (Taylor-Hobson, UK), with a lateral resolution of 0.5 µm.…”
Section: Wear Testing Nanoindentation and Fracture Toughnessmentioning
confidence: 99%